A mímica no teatro e construção de um personagem mímico - Barreto, César Andrade (2015)
This paper aims to discuss about the mime. We intent to study the meaning of the quotes from some theoretical researchers, historic moments as well as the artists who revolutionized this art from antiquity to the twentieth century. We have the intention to relate different forms and mime approaches and we proposes a reflection about how to build a costume and a mime makeup or any other kind of character through observation. Finally, we try to talk about a personal process of characterization and character building in the class "Figurino e Maquiagem " - 2013.1, presenting in the last pages the script of the presentation "improvised" in the class.